2005
DOI: 10.1103/physrevb.71.155106
|View full text |Cite
|
Sign up to set email alerts
|

Negative refraction in a photonic crystal with a metallic cross lattice basis

Abstract: A metamaterial with a negative effective index of refraction is made from a two-dimensional square lattice photonic crystal with a metallic cross lattice basis. A simple procedure is given to design a negative index band within a desired frequency range. The operating frequency is made sufficiently low so as to avoid high orders of diffraction from a slab. An effective index of −1, which is a requirement for perfect lensing, is designed. In addition, the structure is optimized to exhibit the largest possible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…[17][18][19][20][23][24][25] The use of EFSs in an extended zone scheme allows one to see all of the possibly excited Bloch modes within the crystal. This scheme has also provided a means of explaining observed beam splitting in certain systems, [26][27][28] which can be attributed to multiple Bloch modes satisfying phase-matching conditions and leading to higher orders of refraction. The demonstration of a system which exhibits all of these characteristics ͑positive, negative, and zero refraction, as well as beam splitting͒ is highly dependent on various features of the corresponding equifrequency surfaces ͑EFSs͒ of the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][23][24][25] The use of EFSs in an extended zone scheme allows one to see all of the possibly excited Bloch modes within the crystal. This scheme has also provided a means of explaining observed beam splitting in certain systems, [26][27][28] which can be attributed to multiple Bloch modes satisfying phase-matching conditions and leading to higher orders of refraction. The demonstration of a system which exhibits all of these characteristics ͑positive, negative, and zero refraction, as well as beam splitting͒ is highly dependent on various features of the corresponding equifrequency surfaces ͑EFSs͒ of the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Photonic crystals can have a negative effective index, although the mechanism responsible for the effect is different, and as such they are more prone to practical problems. 8,9 We are interested in developing negative index metamaterials at infrared and optical frequencies. To this end, we have previously reported that a three-dimensional array of dielectric spheres can be made to exhibit an isotropic negative permeability.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have previously reported that a three-dimensional array of dielectric spheres can be made to exhibit an isotropic negative permeability. 10,11 The background theory of the effective permittivity and permeability of dielectric and magnetic spheres was first reported by Lewin. 12 Other reports have also found a negative permeability or negative index by using magnetodielectric 13 or ferroelectric 14 spheres.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much research has gone into the study of optical metamaterials [1][2][3][4][5][6][7][8][9][10][11][12][13]. These are periodic or quasi-periodic assemblies of materials with dissimilar optical properties (complex permittivity and/or complex permeability) for which radiation of wavelength greater than the period of the metamaterial cells experience an effective permittivity and permeability, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…an effective refractive index, not possessed by the original constituents. Structures that have been studied include photonic crystals [6,7,13], loaded transmission line media [8,9], polaritonic resonances in nano-size spheres and cylinders [5,10,11], and frequency selective surfaces (FSSs) [4,12]. Frequency selective surfaces are 2D periodic arrays of cells, where each cell consists of metallic patches or apertures (in metallo-dielectric FSSs) or in a patterned configuration of two dielectrics with different optical properties (in the case of all-dielectric FSSs) [14].…”
Section: Introductionmentioning
confidence: 99%